P269 Perioperative outcomes in patients with Pulmonary Hypertension undergoing non-cardiac non-obstetric surgery in a Designated UK Pulmonary Hypertension Centre. (12th November 2015) - Hewitt, RJ; Dimopoulos, K; Alexander, D; Aw, TC; Finney, S; Alonso-Gonzalez, R; Harries, C; Parfitt, L; Wort, J; Price, L
Abstract : Introduction and objectives: Patients with pulmonary hypertension (PH) represent an extremely high-risk surgical group, with previous reported mortality 7–18%, and predicting perioperative risk is difficult. The aim of this study was to characterise a current cohort of patients with pulmonary hypertension undergoing surgery in a National UK Designated PH centre and to determine predictors of adverse events. Methods: Consecutive patients with PH undergoing non-cardiac, non-obstetric surgery were identified by matching theatre and PH databases between 1 st April 2008 and 1 st April 2015. Demographics, recent echocardiogram, right heart catheterisation, B-natriuretic peptide (BNP), six-minute walk test (6MWT) and World Health Organisation functional class (WHO-FC) on last clinic visit was recorded. Anaesthetic and perioperative details; post-operative management, short-term morbidity and 28-day outcome were recorded. Data are mean±SD or median (range). Results: 37 procedures requiring anaesthesia were identified in 32 patients with PAH (7 idiopathic PAH, 1 PVOD, 24 CHD-PAH, 4 CTD-PAH) and 1 CTEPH. Average age was 44.4 ± 13 years, 27(84%) were female. Baseline preoperative WHO-FC was II (3, 9%), III (28, 88%), IV (1, 3%). Baseline 6MWT distance was 317 ± 68 m; BNP 200 (12–2027) ng/L; RV systolic pressure (RVSP) 85 ± 16 mmHg, tricuspid annular planar systolic excursion (TAPSE) 18 ± 7 mm. Cases including oesophagogastroscopy (n = 4), dental extraction (n = 8) under general anaesthesia (GA) were classified as minor; 6 (16%) including mastectomy, laparotomy and fasciotomy as major surgical procedures. Almost all (95%) were performed under GA; most were elective procedures and were monitored on the high dependency or intensive care unit post-operatively. Cardiovascular perioperative complications occurred in 6 cases (16%) including death in 2 patients (5.4%) in the days following surgery, in both cases related to PH crises, resulting in right ventricular (RV) failure. Baseline parameters of RV function including RVSP, TAPSE and the presence of a pericardial effusion were associated with adverse events. Conclusion: Perioperative mortality in patients with PH remains high, even in the current era. If surgery is deemed essential, PH centres with experts in cardiothoracic anaesthesia and ICU should be involved in preoperative planning with the PH multidisciplinary team guiding appropriate selection of patients, considering pulmonary haemodynamics and indices of RV function, as well as surgical factors.